Peran Maroko Dalam Mempertahankan Wilayah Sahara Barat (Telaah Neo-Realisme: National Interest-Balance of Power) - Adnan Adwitama (Universitas Al Azhar Indonesia, 2022)
The clash between regions Morocco and Western Sahara has been so fierce that it has resulted in a prolonged war. Every camp, both Morocco and Western Sahara, both want to take over the Western Sahara region. Both have their respective support from outside and have not found a bright spot. This study aims to see the role of Morocco in defending the Western Sahara region. The efforts made by Morocco are described in this article. The type of research used is library research or literature review using descriptive analysis methods. The data used by news writers in electronic media, journal articles, theses, theses, and dissertations discussing Morocco and Western Sahara as well as studies on defense and security policies as well as neorealism theory. The theory used is the theory of neorealism on the aspect of national interest-balance of power. The result obtained from the analysis of the conflict between Morocco and Western Sahara is that Morocco's role in balancing forces, Morocco is able to balance truce from within and from outside. Strong Moroccan planning with the establishment of the Royal Advisory Council for Saharan Affairs (CORCAS) as well as external support by building cooperation between superpowers, the United States of America and France to balance United Nation support for Western Sahara and cooperation surrounding countries such as Algeria and Libya.Keywords – Maroko, Sahara Barat, Balance of Power, Neorealism